U.S. Consideration of the Intangible Cultural Heritage Convention - Kurin, Richard (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
UNESCO, the United Nations Educational, Scientific, and Cultural Organization, voted overwhelmingly at the biennial meeting of its General Conference in Paris on October 17, 2003 to adopt a new international Convention for the Safeguarding of Intangible Cultural Heritage. That Convention became international law on April 30, 2006. By the end of 2006 it had been ratified or accepted by 68 countries; today, that number is approaching universal acceptance with more than 160 nations having acceded to the convention. At the 2003 session, some 120 nation-members voted for the convention; more registered their support subsequently. No one voted against it; only a handful of nations abstained – Australia, Canada, the United Kingdom, and the United States among them. Within some of those nations, debate over whether to ratify the treaty continues. In this paper, the author considers the convention and unofficially examines the U.S. government position with regard to why support for it was withheld in 2003, how deliberations have proceeded since then, and whether or not the U.S. might ultimately accept the treaty.